Enhanced capacity retention of NCM batteries through doping optimization - Zhang, Xing (Transactions on Environment, Energy and Earth Sciences, 2026)
Nowadays, People are very concerned about the range of electric vehicles, and scientists are also working hard to study how to increase the range. At present, among various methods to enhance energy density, replacing electrode materials is the most common. For instance, nickel get high capacity, the most common nickel-containing battery is NCM (LiNixCoyMnzO2) battery. During the charging and discharging process of NCM batteries, lattice distortion is prone to occur, leading to the collapse of the layered structure and the generation of microcracks. By doping large-radius ions to support the lattice structure, phase transition is suppressed and stress accumulation is reduced. Herein, among several solutions, the doping methods are analyzed emphatically. By consulting literature, based on XRD and other images, various doped elements are analyzed, and the retention rates of capacitance is analyzed to theoretically verify the bias of NCM on doped elements. This paper also proposes a hypothetical combination of doping methods and nanotechnology, aiming to address the expansion of some doped elements, such as silicon, through the characteristics of nanometers.